2020
DOI: 10.1515/cdbme-2020-3066
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automatic decision-making process in histopathological specimens from Barrett’s carcinoma patients using hyperspectral imaging (HSI)

Abstract: Discrimination of malignant and non-malignant cells of histopathologic specimens is a key step in cancer diagnostics. Hyperspectral Imaging (HSI) allows the acquisition of spectra in the visual and near-infrared range (500-1000nm). HSI can support the identification and classification of cancer cells using machine learning algorithms. In this work, we tested four classification methods on histopathological slides of esophageal adenocarcinoma. The best results were achieved with a Multi-Layer Perceptron. Sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Furthermore, in this study and in Hu et al, a realistic LOPOCV was done 13 . This work was based on a previous study, which had shown the best performance for tumor cell identification by a neuronal network with a MLP algorithm 21 . Additionally, SVM and LR models have been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in this study and in Hu et al, a realistic LOPOCV was done 13 . This work was based on a previous study, which had shown the best performance for tumor cell identification by a neuronal network with a MLP algorithm 21 . Additionally, SVM and LR models have been used.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SVM and LR models have been used. By evaluating the data in a grid seach cross-validation a MLP showed the highest sensitivity of 90% 21 . The sensitivity for the cohort investigated here was 77% for EAC and tumor stroma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens from gastric cancer patients were stained with hematoxylin and eosin (HE). Areas with healthy gastric mucosa ( a ) and gastric cancer (GC) ( b ) were selected and imaged by a HSI camera as described previously [ 50 ]. The RGB images were reconstructed.…”
Section: Figurementioning
confidence: 99%